Integrating AR/VR into 21st-century flipped classrooms: Enhancing engagement, HOTS, and English vocabulary mastery in young learners - Bunga Ayu Lolyta; Wiyaka Wiyaka; Lusia Maryani Silitonga (EduLite: Journal of English Education, Literature and Culture, 2026)
The growing demand for 21st-century learning highlights the need for instructional approaches that actively engage young learners while supporting higher-order thinking and language development. Although flipped classrooms and AR/VR technologies have independently demonstrated educational benefits, limited research has examined their combined effects in early English learning contexts. This study investigated the impact of integrating AR/VR tools into a flipped classroom on young learners’ engagement, higher-order thinking skills (HOTS), and vocabulary mastery. A mixed-methods quasi-experimental design was employed involving 60 elementary school students assigned to an experimental group and a control group. Quantitative data were collected through pre- and post-tests and analyzed using ANCOVA and regression analyses. Qualitative data were gathered through semi-structured interviews and analyzed thematically using MAXQDA 2024 to explore learners’ experiences and perceptions. The quantitative findings indicated that students in the experimental group achieved significantly higher outcomes than those in the control group in HOTS (F (1,57) = 15.401, p < .001, η² = .270), English vocabulary mastery (F (1,57) = 22.865, p < .001, η² = .290), and learner engagement (F (1,57) = 32.085, p < .001, η² = .334). The qualitative results supported these findings by revealing strong learning interest, active participation, and increased speaking comfort among learners. Students also demonstrated engagement in sentence construction and self-correction processes, reflecting emerging higher-order thinking skills. Furthermore, the visual and interactive features of AR/VR flashcards were perceived as helpful for vocabulary learning, although some learners reported occasional difficulties requiring assistance. Overall, the integration of AR/VR tools in a flipped classroom created an engaging and supportive learning environment that enhanced young learners’ engagement, thinking skills, and English vocabulary mastery. These findings highlight the pedagogical potential of AR/VR-supported instruction for elementary-level EFL learning.